e-Service Quality and e-Trust Models in Increasing Generation Z e-Customer Satisfaction in e-Wallet Transactions with ShopeePay Application - Syifa Pramudita Faddila; Laras Ratu Khalida; Robby Fauji (Jurnal Mantik, 2022)
The rapid development of the digital world, one of which is marked by changes in traditional transactions to digital transactions through digital wallets (e-Wallet). E-Wallet competition in Indonesia is quite tight, ShopeePay has decreased its position in terms of the most frequently used e-Wallet in 2020 and 2021. So it is necessary to do further research as an effort to increase e-Customer Satisfaction through e-Service Quality variables and e-Trust especially among Generation Z as a characteristic that is close to the digital world. The study was conducted on 166 students of the Management Study Program at the University of Buana Perjuangan Karawang class of 2019 – 2021 who are Generation Z and active users of ShopeePay. This study uses multiple linear regression analysis. The results of the study explain that e-Service Quality and e-Trust have a significant effect on e-Customer Satisfaction either partially or simultaneously. The higher the e-Service Quality and e-Trust provided by the company to consumers, the higher the e-Customer Satisfaction for Generation Z users of the ShopeePay application e-Wallet.